2013
DOI: 10.1002/cld.251
|View full text |Cite
|
Sign up to set email alerts
|

Primary sclerosing cholangitis during childhood and adolescence

Abstract: http://onlinelibrary.wiley.com/journal/10.1002/(ISSN)2046-2484/homepage/2-5-reading-miloh.htm a video presentation of this article http://onlinelibrary.wiley.com/journal/10.1002/(ISSN)2046-2484/homepage/2-5-interview-miloh.htm the interview with the author https://www.wileyhealthlearning.com/Activity/1976014/Activity.aspx

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 13 publications
0
2
0
Order By: Relevance
“…However, it must not be forgotten that MRCP may be negative in small duct PSC, as Miloh’s studies confirm. He demonstrated lesions in the MRCP of 70% of patients with PSC [ 53 , 54 ]. Transabdominal US is considered to be the first line imaging modality in children, and in the presented group it was performed in all patients, although only 32% US exams showed various bile duct abnormalities.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, it must not be forgotten that MRCP may be negative in small duct PSC, as Miloh’s studies confirm. He demonstrated lesions in the MRCP of 70% of patients with PSC [ 53 , 54 ]. Transabdominal US is considered to be the first line imaging modality in children, and in the presented group it was performed in all patients, although only 32% US exams showed various bile duct abnormalities.…”
Section: Discussionmentioning
confidence: 99%
“…In all their patients with suspected PSC, Miloh et al confirmed abnormalities in the histopathological examination of the liver, mainly in the form of varying degrees of fibrosis and cirrhosis. “Onion skin” fibrosis, characteristic for PSC was confirmed in only 26.7% [ 53 , 54 ].…”
Section: Discussionmentioning
confidence: 99%